Can administrative data be used to measure chemotherapy side effects?. (April 2015) - Pearce, Alison; Haas, Marion; Viney, Rosalie; Haywood, Philip; Pearson, Sallie-Anne; van Gool, Kees; Srasuebkul, Preeyaporn; Ward, Robyn
Abstract : Many of the issues with using data from clinical trials and observational studies for economic evaluations are highlighted in the case of chemotherapy side effects. We present the results of an observational cohort study using linked administrative data. The chemotherapy side effects identified in the administrative data are compared with patient self-reports of such events. The results of these comparisons are then used to guide a discussion of the issues surrounding the use of administrative data to identify clinical events for the population of economic models. Although the advantages of easy access and generalizability of the results make administrative data an attractive option for populating economic models, this is not always possible because of the limitations of these data.